The Impact of Expedited Land Title Transfers on Legal Certainty and Ownership Disputes - Fransina Bikio; Sasea, Enny Martha; Ramadhan, Gilang (Indonesian Scientific Publication, 2024)
This research examines the legal impact of rapid land title transfers in Indonesia, which often neglect the detailed verification stage, leaving the door open for unauthorized parties to claim ownership or for entitled parties to be unfairly disenfranchised. The purpose of this research is to explore the conformity of the process of expeditious land title transfers with applicable legal provisions and identify the legality and legal consequences arising from such title transfers. This research utilizes a normative legal method with a descriptive-analytical approach. Primary data includes relevant laws and regulations such as the Basic Agrarian Law (UUPA) No. 5 of 1960 and the Government Regulation on Land Registration, as well as relevant jurisprudence. Secondary data consists of law books, law journals, scientific articles, and previous research reports that discuss similar topics. The results show that accelerated transfers of land rights that disregard legal procedures can lead to legal uncertainty and harm to entitled parties, thus requiring stricter law enforcement and more transparent procedures to ensure legality and fairness in every land transaction.